Tripartite Motif Protein 6 Promotes Colorectal Cancer Cell Migration and Metastasis via SOCS2-STAT3 Signaling - Zhao, Hongjian; Huang, Junjun; Chen, Ming; Li, Baoru; Chen, Xinran; Zhou, Mingqing (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the leading causes of cancer death worldwide, with most mortalities being caused by metastases. However, the underlying molecular mechanism of CRC metastases remains largely unknown. Emerging evidence has shown the role of the tripartite motif family, especially tripartite motif protein 6 (TRIM6), in carcinogenesis. In this study, we used CRC cell lines with TRIM6 knockdown and overexpression to investigate the function of TRIM6 in CRC metastasis. We found that TRIM6 promotes CRC cell migration and invasion both in vitro and in vivo. TRIM6 knockdown slows down the migration and invasion processes, whereas TRIM6 overexpression accelerates CRC cell migration and invasion. TRIM6 is potentially the upstream regulatory factor for signal transducer and activator of transcription 3 (STAT3) via the suppressor of cytokine signaling 2 (SOCS2). A total of 70 samples from patients with CRC further confirmed that TRIM6 expression level is positively correlated with STAT3 phosphorylation and negatively correlated with SOCS2 expression. Therefore, TRIM6 could be a potential therapeutic target for CRC metastasis.